2018
DOI: 10.3390/ijerph15020193
|View full text |Cite
|
Sign up to set email alerts
|

“Girls Have More Challenges; They Need to Be Locked Up”: A Qualitative Study of Gender Norms and the Sexuality of Young Adolescents in Uganda

Abstract: Unequal power and gender norms expose adolescent girls to higher risks of HIV, early marriages, pregnancies and coerced sex. In Uganda, almost half of the girls below the age of 18 are already married or pregnant, which poses a danger to the lives of young girls. This study explores the social construction of gender norms from early childhood, and how it influences adolescents’ agency. Contrary to the mainstream theory of agency, which focuses on the ability to make informed choices, adolescents’ agency appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 25 publications
3
56
0
4
Order By: Relevance
“…Findings from a qualitative study in Uganda indicate use of media with sexual content is perceived to contribute to persistence of inequitable norms, especially in depicting women as submissive and men being sex driven [ 33 ]. In another study in a subset of these VYAs, we found inequitable sexual socialization tendencies beginning to emerge in early adolescence [ 25 ]. Both of these studies highlighted the role that media can play in shaping VYAs ideas about sex and relationships including norms that can be harmful to both boys and girls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings from a qualitative study in Uganda indicate use of media with sexual content is perceived to contribute to persistence of inequitable norms, especially in depicting women as submissive and men being sex driven [ 33 ]. In another study in a subset of these VYAs, we found inequitable sexual socialization tendencies beginning to emerge in early adolescence [ 25 ]. Both of these studies highlighted the role that media can play in shaping VYAs ideas about sex and relationships including norms that can be harmful to both boys and girls.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 7.6% of VYAs were sexually active, which is lower than previous findings among the same age group in Sub-Saharan Africa of 11–15% [ 23 , 37 ]. More boys than girls reported being sexually active, which may relate to underreporting among Ugandan girls, who are often less comfortable and more stigmatized for being sexually active before marriage [ 25 ] . However, it was noted in this study that the majority of sexually active young adolescents did not use condoms, which puts young adolescents at risk of STIs, HIV and early pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These same norms serve to maintain a shroud of silence around various harmful and sometimes life threatening practices affecting girls. Ninsiima et al (2018) warn that gendered norms that taboo access to sexuality information for girls fail to create a safe environment for fostering girls' agency and well-being. Acts of GBV pose serious threats to girls' mental and physical wellbeing.…”
Section: Regional Instruments Include: African Commission On Human Anmentioning
confidence: 99%
“…Ninsiima et al [ 4 ] went deep into the gender aspect in developing countries with their report from Uganda and wrote a paper titled “Girls Have More Challenges; They Need to Be Locked Up”: A Qualitative Study of Gender Norms and the Sexuality of Young Adolescents in Uganda. Unequal power and gender norms expose adolescent girls to high risks of HIV, early marriages, pregnancies and coerced sex.…”
mentioning
confidence: 99%